2019
DOI: 10.1038/s41598-018-36975-z
|View full text |Cite
|
Sign up to set email alerts
|

Global Variation of Nutritional Status in Children Undergoing Chronic Peritoneal Dialysis: A Longitudinal Study of the International Pediatric Peritoneal Dialysis Network

Abstract: While children approaching end-stage kidney disease (ESKD) are considered at risk of uremic anorexia and underweight they are also exposed to the global obesity epidemic. We sought to investigate the variation of nutritional status in children undergoing chronic peritoneal dialysis (CPD) around the globe. The distribution and course of body mass index (BMI) standard deviation score over time was examined prospectively in 1001 children and adolescents from 35 countries starting CPD who were followed in the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 25 publications
2
15
0
5
Order By: Relevance
“…It is also assumed that nutrition adequacy is essential to promote growth and development of children with CKD. However, it has been demonstrated that aggressive enteral feeding in infants with CKD stage 5 on peritoneal dialysis may result in excessive weight gain with rather limited effects on longitudinal growth (26,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also assumed that nutrition adequacy is essential to promote growth and development of children with CKD. However, it has been demonstrated that aggressive enteral feeding in infants with CKD stage 5 on peritoneal dialysis may result in excessive weight gain with rather limited effects on longitudinal growth (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) in pediatric and adult patients is characterized by a progressive decline in kidney function, classified according to the Kidney Disease: Improving Global Outcomes (KDIGO) in a system based primarily on glomerular filtration rate (eGFR, ml/min/1.73 m 2 ) and on proteinuria (1). The classification consists of 5 stages based on a decreasing of eGFR: G1 normal or high (≥ 90); G2 mildly decreased (60-89); G3a mildly to moderately decreased (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59); G3b moderately to severely decreased (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44); G4 severely decreased (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and G5 kidney failure (≤ 15, or dialysis) (1). According to these Guidelines, CKD should be established based on kidney function and damage expressed as eGFR, irrespective of...…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that gastrostomy placement can induce GER and, in fact, there is some evidence that gastrostomy feeding may reduce or prevent vomiting [4]. An NG tube may stent open the gastro-esophageal junction, increasing any tendency to vomiting and GERD [3].…”
Section: Evidence and Rationalementioning
confidence: 99%
“…For example, in a study from the International Pediatric Peritoneal Dialysis Network (IPPN) of growth in children under 2 years of age on peritoneal dialysis (PD), tube feeding was predominantly used in North America and Europe, with very little usage elsewhere in the world [3]. Similarly, in a second IPPN study in older children, enteral tube feeding was rarely applied in Central Europe, Turkey, India, South East Asia, and China [4]. KDOQI did not guide readers in the type of enteral feeding device to choose.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is also associated with worsening uremic symptoms and can lead to protein-energy wasting and increased mortality. Conversely, obesity is a worldwide problem that is also increasingly affecting the CKD population (2).…”
Section: Introductionmentioning
confidence: 99%